A profile of multiple intelligence for high achievers and normal students - a case study in Sarawak - Shariffudin, Rio Sumarni; Lee, Ming Foong (Persatuan Teknologi Pendidikan Malaysia, 2007)
Many research findings have shown that learners encountered many learning difficulties. However, for effective learning one has to know oneself and having knowledge about one’s strengths and weaknesses. The process of teaching and learning will be more effective and meaningful when teachers and learners know their potential, their unique styles, strengths and weaknesses in learning. Howard Gardner's theory of multiple intelligences is a psychological and educational theory espousing that ten types of "intelligence" exist in humans, each relating to a different sphere of human life and activity. Nowadays, how learners interpret knowledge differs greatly from what used to be perceived by the teachers. Also how the teachers deliver the knowledge may not match the expectations of the learners. As a result, teachers’ instructional methods became inefficient and learners failed to learn. The dramatic change in learners should be balanced by an equal change in teachers’ instruction especially among high achievers. This paper examines the Multiple Intelligences pattern among the high achievers and the normal student. This research compares between the high achievers and the normal students with respect to their preferences of learning style. The respondents comprised 150 normal students and 160 high achievers from secondary schools around Sarawak. The Multiple Intelligences Inventory was modified and validated according to the research needs. The results showed that the normal students posses the following intelligences: Interpersonal> Bodily/Kinesthetic > Musical/Rhythmic > Visual/Spatial> Verbal/Linguistic = Logical/Mathematical > Intrapersonal> Naturalist. Whilst for high achievers posses the following intelligences: Interpersonal> Logical/Mathematical > Intrapersonal> Visual/Spatial> Verbal/Linguistic> Naturalist> Musical/Rhythmic> Bodily/Kinesthetic. Based on these result, a theorectical framework was proposed to develop a software to match students’ learning styles (Multiple Intelligence) with computer and web-based learning environments. Through an awareness of preferred learning styles and environments, more effective learning environments can be set up to assist students in their learning.